Detection of Formaldehyde in Water: A Shape-Effect on the Plasmonic Sensing Properties of the Gold Nanoparticles - Sri Nengsih; Akrajas Ali Umar; Munetaka Oyama; Muhamad Mat Salleh (Sensors, 2012)
The effect of morphology on the plasmonic sensing of the presence of formaldehyde in water by gold nanostructures has been investigated. The gold nanostructures with two different morphologies, namely spherical and rod, were prepared using a seed-mediated method. In typical results, it was found that the plasmonic properties of gold nanostructures were very sensitive to the presence of formaldehyde in their surrounding medium by showing the change in both the plasmonic peaks position and the intensity. Spherical nanoparticles (GNS), for example, indicated an increase in the sensitivity when the size was increased from 25 to 35 nm and dramatically decreased when the size was further increased. An m value, the ratio between plasmonic peak shift and refractive index change, as high as 36.5 nm/RIU (refractive index unit) was obtained so far. An expanded sensing mode to FD was obtained when gold nanostructures with nanorods morphology (GNR) were used because of the presence of two plasmonic modes for response probing. However, in the present study, effective plasmonic peak shift was not observed due to the intense plasmonic coupling of closely packed nanorod structures on the surface. Nevertheless, the present results at least provide a potential strategy for response enhancement via shape-effects. High performance plasmonic sensors could be obtained if controlled arrays of nanorods can be prepared on the surface.